IA - lider . IA - lider . I Am a Leader . Я - лидер - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. TV- game show for politicians. The participants are Ivan Rybkin and Stepan Orlov. Contributors: Afanas'ev, Aleksandr (Anchor) Телеигра для политиков. Участники - Иван Рыбкин, и Степан Орлов. Создатели: Афанасьев, Александр (Ведущий/Ведущая)